Job Satisfaction of Private Teachers: The Role of Compensation, Work Environment, and Motivation from a Two-Factor Theory Perspective - Aisyah, Siti Nur; Yuswono , Irawan (PT. Anagata Sembagi Education, 2025)
This study aims to examine the influence of compensation and work environment on job satisfaction among private school teachers, with work motivation serving as a mediating variable. The research was conducted in the regions of Brebes, Tegal, and Tegal City using a quantitative approach. Data were collected through questionnaires distributed to 186 respondents and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that both compensation and work environment have a positive and significant impact on work motivation and job satisfaction. Furthermore, work motivation significantly affects job satisfaction and mediates the relationship between hygiene factors and satisfaction. These findings reinforce the relevance of the Two-Factor Theory in explaining the dynamics of job satisfaction in the private education sector. The study implies the need for integrative managerial policies that combine structural support with psychological reinforcement to enhance the well-being and performance of private school teachers.